2001
DOI: 10.1111/j.1349-7006.2001.tb01156.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA Sequence Copy Number Aberrations Associated with Histological Subtypes and DNA Ploidy in Gastric Carcinoma

Abstract: We have analyzed DNA sequence copy number aberrations (DSCNAs) and DNA ploidy by using comparative genomic hybridization and laser scanning cytometer in gastric carcinomas (GCs) to elucidate the genomic aberrations in relation to clinicopathological parameters. Thirty-two out of 33 cases showed one or more DSCNAs with a mean number of 11.7 per tumor. High-level gains were detected at 2p, 3q, 6p, 7p, 7q, 8q, 12p, 13q, 19q, and 20q. Frequency of gross genomic abnormalities and chromosome regions that have genomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 34 publications
3
15
0
Order By: Relevance
“…(19,20) Each type reveals different characteristics with regard to clinicopathological parameters and genetic differences, and candidate genes responsible for those phenotypic differences have been proposed. (2,(21)(22)(23)(24) The ability of CGH-arrays to differentiate among histological types of renal cancer (25) suggested that we might be able to identify novel genes involved in different histological types of GC by CGH-array analysis. According to the degree of differentiation, we classified 28 of our GC cell lines into well-differentiated and undifferentiated types, on the basis of the diagnoses of the primary tumors from which they were derived, and compared their patterns of copy-number aberrations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(19,20) Each type reveals different characteristics with regard to clinicopathological parameters and genetic differences, and candidate genes responsible for those phenotypic differences have been proposed. (2,(21)(22)(23)(24) The ability of CGH-arrays to differentiate among histological types of renal cancer (25) suggested that we might be able to identify novel genes involved in different histological types of GC by CGH-array analysis. According to the degree of differentiation, we classified 28 of our GC cell lines into well-differentiated and undifferentiated types, on the basis of the diagnoses of the primary tumors from which they were derived, and compared their patterns of copy-number aberrations.…”
Section: Resultsmentioning
confidence: 99%
“…(6) Furthermore, according to association between chromosomal aberrations and histological subtypes (well-and undifferentiated type) of GC cell lines, our data also included the loci, which had been detected by analyses of primary GC samples, such as gain of 20q and loss of 8p in intestinal type GC and gain of 7q in diffuse tumors. (20,21) However, small copy-number changes, even gain or loss of only one copy within a small region that was never detected by conventional CGH, were revealed by our custom-made CGHarray. We were able to discriminate independent amplifications of multiple target genes in the same region, such as CDK6 and MET at 7q, which formerly were recognized as one amplicon by conventional CGH.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in this study, we have shown that the increased risk of lymph node metastasis associated with the homozygous 279R-574P haplotype is mainly in the diffuse type of gastric cancer. Several reports from other laboratories have suggested that the MMP-9 overexpression mainly occurs in the intestinal type (7,34) and that the association of overexpression with lymph node metastasis is restricted to the intestinal type (20). Combined with the findings from this study, a hypothesis can be constituted that the quantitative and qualitative aspects exert their effects complementarily.…”
Section: Discussionmentioning
confidence: 99%
“…iGCs form cohesive gland-like tubular structures, whereas dGCs exhibit minimal cell cohesion with frequent invasion into surrounding tissues (11). Although amplifications at 17q12-21 and 20q and losses at 8p and 9p are more frequently observed in iGC, 8p and 12q gains are associated with dGC (12,13), arguing that iGC and dGC may represent molecularly distinct entities. Furthermore, ERBB2/HER2 amplifications are observed in iGC but not dGCs, raising the possibility that only the former may be candidates for Trastuzumab (anti-HER2) therapy (14).…”
Section: Introductionmentioning
confidence: 94%